Does broadband speed really matter for driving economic growth? Investigating OECD countries - Ibrahim Kholilul Rohman; Erik Bohlin (International Telecommunications Society (ITS), 2012)
This paper aims to measure the impact of broadband speed on economic growth in the OECD countries. The macroeconomic indicators for this study were collected from OECD databases, except for the speed data, which were gathered from Ookla, a company that provides broadband testing and web-based network diagnostic applications data on a daily basis. With this, quarterly balanced panel data for 34 OECD countries during the period 2008-2010 were examined. The study found that the estimated coefficient of broadband speed is statistically significant. Doubling the broadband speed will contribute to 0.3% growth compared with the growth rate in the base year. The results convey that the impact of increasing broadband speed on GDP growth will largely depend on two aspects: (i) the size of the coefficient of the broadband speed (beta) and (ii) the existing economic growth in each country. Consequently, since the coefficient is linear, the impact will also be relatively greater for countries that experienced lower economic growth during previous years. Finally, the paper provides suggestions for future research in this vein and further calibration of future models.
Keywords: 330; broadband; speed; economic growth; OECD; panel data; fixed effect; advertised speed; measured speed